Electromyographic study of the trapezius (pars superior) and serratus anterior (pars inferior) in free movements of the arm - Longo Bull, M.; De Freitas, V.; Vitti, M. (My University, 1990)
The emg activity of the trapezius (pars superior) and serratus anterior (parts inferior) mm. in free movements of the arm was examined in 25 young adult volunteers of both sexes, using a 2-channel TECA TE4 electromyograph with single coaxial needle electrodes. The records obtained showed that: 1) In abduction, flexion, adduction and extension of the arm, TS and SI act synergically; 2) The activity of both muscles increases gradually in abduction and flexion when the scapular rotation occurs. TS also acts as scapular elevator, a movement which occurs simultaneously with abduction and flexion; 3) the activity of both muscles decreases gradually in adduction and extension which controls the return of the scapula and clavicle to the initial position; 4) In hyperextension TS and SI are inactive.